1996
DOI: 10.1159/000217198
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Low-Molecular-Weight Heparin versus Standard Heparin and the Prevention of Thromboembolism in Medical Inpatients

Abstract: In a multicenter, double-blind clinical trial in 1,968 inpatients 1 daily subcutaneous administration of LMW heparin plus 2 placebo injections or 3 × 5,000 IU unfractionated (UF) heparin was given for 10 (8-11) days. The primary end point was the incidence of proximal deep-vein thrombosis or pulmonary embolism. Patients were assessed during the study period for development of proximal deep-vein thrombosis by compression sonography at days 1 and 10 and for pulmonary embolism by scintigraphy in symptomatic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 22 publications
2
66
0
4
Order By: Relevance
“…Of these, 13 articles were excluded because of an inappropriate patient population (studies evaluating treatment of venous thromboembolism, n ϭ 8; acute coronary syndrome, n ϭ 4; hemodialysis, n ϭ 1); 11 articles were excluded because of the absence of comparison between UFH and LMWH; 32 articles were excluded because no quantitative results were reported on HIT or thrombocytopenia; 12 articles were excluded because of an undefined threshold for thrombocytopenia; 3 RCTs measuring thrombocytopenia were excluded because their definitions of thrombocytopenia were considered inadequate (platelet counts less than 70 ϫ 10 9 /L, less than 80 ϫ 10 9 /L, and less than 50 ϫ 10 9 /L, respectively). [6][7][8] One article 9 was excluded because of significant overlap of the reported patients between it and a previous study. One nonrandomized study comparing HIT incidence with LMWH and UFH was excluded because it had been published in abstract form only and appropriate data could not be extracted 10 ; 2 articles were meta-analyses; one article was a review.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 13 articles were excluded because of an inappropriate patient population (studies evaluating treatment of venous thromboembolism, n ϭ 8; acute coronary syndrome, n ϭ 4; hemodialysis, n ϭ 1); 11 articles were excluded because of the absence of comparison between UFH and LMWH; 32 articles were excluded because no quantitative results were reported on HIT or thrombocytopenia; 12 articles were excluded because of an undefined threshold for thrombocytopenia; 3 RCTs measuring thrombocytopenia were excluded because their definitions of thrombocytopenia were considered inadequate (platelet counts less than 70 ϫ 10 9 /L, less than 80 ϫ 10 9 /L, and less than 50 ϫ 10 9 /L, respectively). [6][7][8] One article 9 was excluded because of significant overlap of the reported patients between it and a previous study. One nonrandomized study comparing HIT incidence with LMWH and UFH was excluded because it had been published in abstract form only and appropriate data could not be extracted 10 ; 2 articles were meta-analyses; one article was a review.…”
Section: Resultsmentioning
confidence: 99%
“…A randomized, double-blind controlled trial in 442 hospitalized elderly patients bedridden for acute illness demonstrated similar efficacy of enoxaparin 20 mg once daily compared with LDUH 5000 U twice daily. 64 66 Although the results including all patients demonstrated equivalence between the 2 therapies in incidence of venographically detected VTE, in the subset of 206 patients with HF, enoxaparin was associated with a numerically lower incidence of VTE (9.7% versus 16.1%, Pϭ0.0139 for equivalence). No patients with HF developed PE during enoxaparin therapy, whereas 1 patient in the LDUH group was found to have PE on autopsy.…”
Section: Studies Comparing Lduh and Lmwhmentioning
confidence: 93%
“…58,[61][62][63][64][65][66][67][68] A randomized, double-blind controlled trial in a high-risk group of 959 hospitalized medical patients compared enoxaparin 40 mg once daily with LDUH 5000 U three times daily. Enoxaparin was found to be at least as efficacious as LDUH with fewer adverse events.…”
Section: Studies Comparing Lduh and Lmwhmentioning
confidence: 99%
“…However, generalizing our results to include other LMWHs is difficult given the limited data available regarding comparative efficacies (most studies compare LMWHs with placebo or UFH) and the different regimens used. These results may not transfer directly to cases where other LMWHs did not show superiority compared with UFH for VTE prophylaxis in medical patients [25,26].…”
Section: Discussionmentioning
confidence: 80%